Q: What is 6y-5 equals 8 plus 10y?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

x = 6y = 89x + 10y = 9(6) + 10(8) = 54 + 80 = 134

Multiply the first by 8 and the second by 3

6y-5=8+10y 6y-10y=8+5 -4y=13 y=-3.,25 because: 6*3.25-5=-24,5 and 8+10*3.25=-24,5 true

y + x = 9 10y + 20x = 100 This is a basic linear system of equalities. We can start by rewriting the first equation as: -10y - 10x = -90 by multiplying the equation by -10, from here we can eliminate y and solve for x (-10y - 10x = -90) + (10y + 20x = 100) = (10x = 10) This yields x = 1, and by plugging x into the first equation y = 8

you have to bring the "y" to one side. 10y - 6 = 2 + 4y 10y-4y = 2 + 6 6y = 8 y = 8/6 If you substitute 8/6 into y you will find that 8/6 is the answer

Related questions

x = 6y = 89x + 10y = 9(6) + 10(8) = 54 + 80 = 134

Multiply the first by 8 and the second by 3

6y-5=8+10y 6y-10y=8+5 -4y=13 y=-3.,25 because: 6*3.25-5=-24,5 and 8+10*3.25=-24,5 true

You're there. 4x = 10y - 8.[so subtract 10y from both sides, 4x - 10y = -8]multiply b.s. by -1 , gives -4x +10y = 8

y + x = 9 10y + 20x = 100 This is a basic linear system of equalities. We can start by rewriting the first equation as: -10y - 10x = -90 by multiplying the equation by -10, from here we can eliminate y and solve for x (-10y - 10x = -90) + (10y + 20x = 100) = (10x = 10) This yields x = 1, and by plugging x into the first equation y = 8

(y - 8)(y - 2)

you have to bring the "y" to one side. 10y - 6 = 2 + 4y 10y-4y = 2 + 6 6y = 8 y = 8/6 If you substitute 8/6 into y you will find that 8/6 is the answer

If x = 8 and y = 10 then it is 44.

It is the property that equals plus equals are equals.

(y - 8)(y - 2)

x + 2y = -5 2x + 3x = -9 5x = -9 x + 2y = -5 x = -2y - 5 5(-2y - 5) = -9 -10y - 25 = -9 -10y = 16 y = -5/8 x = -2y - 5 x = -2(-5/8) - 5 x = -5/4 - 5 x = -25/4 (-25/4, -5/8)

it is 28